The impact of phonological versus semantic repetition training on generalisation in chronic stroke aphasia reflects differences in dorsal pathway connectivity. Issue 4 (19th May 2018) - Holland, Rachel; Johns, Sasha L.; Woollams, Anna M.
ABSTRACT: It has been suggested that neuroimaging can be used to inform therapeutic intervention. The current study aimed to determine whether an individual would benefit more from training engaging their intact or their damaged neural pathway. Two males with chronic stroke aphasia participated, with DM showing milder disruption of connectivity along the dorsal language pathway relative to JS, according to distortion corrected diffusion-weighted magnetic resonance imaging. Each patient received two blocks of six repetition training sessions over two weeks, one of which was "phonological" and the other "semantic" in nature. Both phonological and semantic training produced significant gains for both patients for trained items. For the untrained control items, significant gains were specific to training type for each patient. Only phonological training elicited significant generalisation for DM, which was greater than that seen for JS. Conversely, only semantic training elicited significant generalisation for JS, which was greater than that seen for DM. This double dissociation in generalisation effects suggests that a restitutive approach is more effective for patients with milder damage while a compensatory approach may be more effective for those with more severe damage. These results indicate the utility of neuroimaging to optimise relearning strategies and promote generalisation to untrained items.